Regulation of T Follicular Helper Cells in Islet Autoimmunity - Serr, Isabelle; Daniel, Carolin (Frontiers in Immunology, 2018)
T follicular helper (TFH) cells are an integral part of humoral immunity by providing help to B cells to produce high-affinity antibodies. The TFH precursor compartment circulates in the blood and TFH cell dysregulation is implied in various autoimmune diseases including type 1 diabetes (T1D). Symptomatic T1D is preceded by a preclinical phase (indicated by the presence of islet autoantibodies) with a highly variable progression time to the symptomatic disease. This heterogeneity points towards differences in immune activation in children with a fast versus slow progressor phenotype. In the context of T1D, previous studies on TFH cells have mainly focused on the clinically active state of the disease. In this review article we aim to specifically discuss recent insights on TFH cells in human islet autoimmunity before the onset of symptomatic T1D. Furthermore, we will highlight advances in the field of TFH differentiation and function during human islet autoimmunity. Specifically, we will focus on the regulation of TFH cells by microRNAs (miRNAs), as well as on the potential use of miRNAs as biomarkers to predict disease progression time and as future drug targets to interfere with autoimmune activation.